Signal Detection Report: Light therapy for non-seasonal depression - Pratt, Misty; Ahmadzai, Nadera; Hutton, Brian; Wieland, Susan; Skidmore, Becky; Moher, David (Université d'Ottawa | University of Ottawa, 2017)
Previous research evaluating a cohort of published systematic reviews demonstrated that 7% of reviews were out of date by the time of publication, while as many as 23% went out of date within two years of being completed. The utility of systematic review-based evidence depends on their remaining up-todate. As such, the Cochrane Complementary Medicine Field and the Knowledge Synthesis group at the Ottawa Hospital Research Institute (OHRI) have determined a set of existing reviews of interest for which signal detection work using the Ottawa Method’s qualitative/quantitative signal detection approach has been performed. The Ottawa method involves identification of qualitative and quantitative signals/triggers indicating the need of updating of a systematic review. The Ottawa method has been used to assess the need for updating systematic reviews in the past. A graphical overview of our approach and application of the Ottawa signal detection method is provided in Appendix A, Figure 1 of this report. This work assessed potential triggers signifying the need for updating of six past Cochrane Complementary Medicine reviews. The conclusion as to whether or not each of the reviews is in need of updating was made based on the identification of qualitative and quantitative signals.